2015
DOI: 10.5195/ijms.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Congenital Anomalies in Newborns and Its Relation to Maternal Health in a Tertiary Care Hospital in Peshawar, Pakistan

Abstract: Background: Congenital anomalies are a major cause of perinatal and neonatal deaths, both in low- and high-income countries. They are relatively common worldwide, affecting 3% to 5% of live births. Methods: A cross-sectional study was conducted from January 2014 to June 2014 at the Khyber teaching hospital in Peshawar. Specific patient information was obtained from patient records at the beginning of the study. Those individuals found to have at least one birth defect were approached and their attendants (moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
4
7
0
Order By: Relevance
“…Polydactyly types were most prevalent, followed by clubfoot, arthrogryposis, reduction defects, and syndactyly types. Most of the limb/digit defects do not cause severe disability and, owing to their minor nature, such anomalies remain less reported in epidemiological studies [12,25,26]. As witnessed in the present cohort, the majority of limb defects were of milder nature and did not result in any disability.…”
Section: Discussionsupporting
confidence: 45%
“…Polydactyly types were most prevalent, followed by clubfoot, arthrogryposis, reduction defects, and syndactyly types. Most of the limb/digit defects do not cause severe disability and, owing to their minor nature, such anomalies remain less reported in epidemiological studies [12,25,26]. As witnessed in the present cohort, the majority of limb defects were of milder nature and did not result in any disability.…”
Section: Discussionsupporting
confidence: 45%
“…Maternal age > 35years was observed to be significantly associated with anomalies of the urogenital system in the present study. This corroborates other studies [28,46,47,48] which also showed increased incidence of CA with increasing maternal age especially in mothers > 35years thus agrees with the known theory of advanced maternal age as a risk of CA [49] In addition, increased maternal age has been associated with an increase in chromosomal meiotic errors [33]. This therefore calls for a high index of suspicion in mothers > 35years who are pregnant.…”
Section: Ga=gestational Age; Dama=discharged Against Medical Advicesupporting
confidence: 91%
“…The reason is not far-fetched as 45% of CA in the latter study was syndromic of which 47% had Down's syndrome which has been associated more with maternal age > 35years. This is because increased maternal age is associated with increase in chromosomal meiotic errors [33].…”
Section: Ga=gestational Age; Dama=discharged Against Medical Advicementioning
confidence: 99%
“…Our study has shown the prevalence of interfamily marriage is 64%. 15 A slight higher prevalence of interfamily marriage (80%) has been observed in Peshawar but Northern Area of India has shown the interfamily marriage is quite different (1-4%) 16 , this is because of religious constraints which refrain them from interfamily marriages. 17,18 The prevalence of interfamily birth defect is varying in different regions like in Pakistan it is higher (11%) and in developed countries it is (6%).…”
Section: Discussionmentioning
confidence: 97%